2021
DOI: 10.1016/j.heliyon.2021.e07491
|View full text |Cite
|
Sign up to set email alerts
|

Geographically weighted bivariate zero inflated generalized Poisson regression model and its application

Abstract: This study discusses the development of Zero Inflated Generalized Poisson Regression (ZIGPR) with two response variables, that is Bivariate ZIGPR (BZIGPR). The extension of the ZIGPR model by considering spatial factor called Geographically Weighted Zero Inflated Generalized Poisson Regression (GWBZIGPR). The GWBZIGPR produces a local parameter estimator for each location of observation. The parameter estimation using the Maximum Likelihood Estimation (MLE) method obtained an equation that did not closed-form … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…Next, as the data showed high spatial autocorrelation of the residuals, GWPR was applied. The GWPR is capable of creating an equation for each municipality and using it with Poisson distribution in order to smooth the inflated number of zero moderate and severe events [ 31 , 32 ]. The regression model that achieved the best performance as defined by the highest adjusted R 2 value, and the lowest value of AIC and Moran’s I residuals was used to make the study analogies [ 29 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Next, as the data showed high spatial autocorrelation of the residuals, GWPR was applied. The GWPR is capable of creating an equation for each municipality and using it with Poisson distribution in order to smooth the inflated number of zero moderate and severe events [ 31 , 32 ]. The regression model that achieved the best performance as defined by the highest adjusted R 2 value, and the lowest value of AIC and Moran’s I residuals was used to make the study analogies [ 29 ].…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, the heterogeneity of worse SBE outcomes in Brazil could PRODOC/FAPEAM, and POSGRAD) and by the Ministry of Health, Brazil (proposal No. 733781/ [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35]. CJG receives research funding and research reported in this publication was partly supported by the Fogarty International Center of the National Institutes of Health under Award Number R21TW011944.…”
Section: Introductionmentioning
confidence: 99%
“…The GWPR model parameter estimation was carried out using the Maximum Likelihood Estimation (MLE) method, namely by maximizing the likelihood function [15]. The MLE method is usually used if the distribution of the data being modeled is known.…”
Section: Geographically Weighted Poisson Regression (Gwpr)mentioning
confidence: 99%
“…The results of hypothesis testing indicate that the K1 -K4 visits has a significant influence on the maternal mortality. To prevent maternal mortality, the government must pay attention to the procedures for antenatal care until delivery (Purhadi et al, 2021). In Indonesia, the k1-k4 examination is highly recommended by the government.…”
Section: Relation Between K1 -K4 Visits and Maternal Mortalitymentioning
confidence: 99%